Composite aluminum current collector, preparation method thereof and lithium ion battery

By covering the AlN passivation film on the surface of the aluminum foil, the corrosion problem of aluminum foil at high voltage and the insufficient conductivity of the current collector are solved, and the conductivity and corrosion resistance of the high-power battery are achieved.

CN119725549APending Publication Date: 2025-03-28SHANGHAI XUANYI NEW ENERGY DEV CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411974365.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-30
Publication Date
2025-03-28

AI Technical Summary

Technical Problem

In the prior art, aluminum foil is corroded at high voltages, and the conductivity of the current collector cannot meet the needs of high-power batteries.

Method used

A layer of AlN passivation film is coated on the surface of the aluminum foil, and a composite aluminum current collector is formed by sonication and soaking, cleaning and sintering steps in the trimethylaluminum liquid.

Benefits of technology

It reduces the corrosion problem of aluminum foil at high voltage, and at the same time improves the conductivity of the current collector, meeting the needs of high-power batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119725549A_ABST
    Figure CN119725549A_ABST
Patent Text Reader

Abstract

The invention provides a composite aluminum current collector, a preparation method thereof and a lithium ion battery. The composite aluminum current collector comprises an aluminum foil and an AlN passive film coated on the surface of the aluminum foil. According to the composite aluminum current collector, the core principle is that the surface of the aluminum foil is coated with the AlN passivation film, and due to the fact that AlN has good electronic conductivity and has high chemical stability and high voltage resistance, the AlN can meet the requirements for conductivity and corrosion resistance at the same time, and therefore the AlN passivation film is coated on the surface of the aluminum foil, the conductivity and corrosion resistance of the composite aluminum current collector are improved, and the service life of the composite aluminum current collector is prolonged. The problem that the aluminum foil is corroded at high voltage is solved, and the conductivity of the current collector is improved, so that the requirement of a high-power battery is met.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of aluminum current collectors, and in particular to a composite aluminum current collector and a preparation method thereof, and a lithium ion battery. Background Art

[0002] Aluminum foil is the most commonly used current collector for lithium battery positive electrode. During the preparation and storage process, the surface of aluminum foil will be oxidized to form a thin passivation layer. This passivation layer ensures that the aluminum foil will not be oxidized within the normal operating voltage range (less than 4.3V vs Li+) without significantly reducing the conductivity of the aluminum foil. + / Li). However, the severe corrosion problem under high voltage and high temperature cannot meet the growing energy density demand of power batteries. The corrosion of aluminum current collector may lead to the delamination of positive electrode, increase of internal resistance, decomposition of electrolyte and other problems, thus leading to premature failure of the battery. In addition, the study found that there is also a clear relationship between the degree of oxidative corrosion of aluminum foil and the lithium salt used in the electrolyte.

[0003] Compared with the LiPF6 salt commonly used in traditional electrolytes, the new LiFSI / LiTFSI salt has an excellent surface in improving battery power performance. However, due to the high solubility of Al(FSI)3 / Al(TFSI)3 in organic solvents, the corrosion of aluminum foil by the electrolyte prepared with the above two lithium salts is aggravated. If the above problems are solved by using surface engineering strategies and using materials such as Al2O3 or AlF3 to construct a surface inert film, although the problem of oxidative corrosion can be solved to a certain extent, the traditional AlF3 or Al2O3 interface has low electronic conductivity, resulting in increased electronic internal resistance, which is not conducive to high-power charging and discharging of the battery. This will damage the power characteristics of the battery. Therefore, it is not appropriate to use such strategies in high-power batteries. Summary of the invention

[0004] The main purpose of the present invention is to provide a composite aluminum current collector, a preparation method thereof, and a lithium ion battery to solve the problems in the prior art that aluminum foil is corroded at high voltage and the conductivity of the current collector cannot meet the requirements of high-power batteries.

[0005] In order to achieve the above object, according to one aspect of the present invention, a composite aluminum current collector is provided, which includes an aluminum foil and an AlN passivation film coated on the surface of the aluminum foil.

[0006] Furthermore, the thickness of the AlN passivation film layer is 5 to 15 nm, preferably 8.9 to 15 nm.

[0007] Furthermore, the electrical conductivity of the composite aluminum current collector is 2500-4005 S / m, preferably 3206-4005 S / m; and / or the resistivity of the composite aluminum current collector is not higher than 4×10 -8Ω·m, preferably 2.69×10 -8 Ω·m~3.56×10 -8 Ω·m.

[0008] According to another aspect of the present invention, a method for preparing the aforementioned composite aluminum current collector is provided, and the preparation method comprises: step S1, performing surface pretreatment on an aluminum foil to obtain a pretreated aluminum foil; step S2, using water as a medium, performing ultrasonic treatment on the pretreated aluminum foil to obtain an ultrasonic aluminum foil; step S3, placing the ultrasonic aluminum foil in a trimethylaluminum liquid for soaking, washing, and sintering in sequence to obtain a composite aluminum current collector.

[0009] Furthermore, in the above step S3, the concentration of the trimethylaluminum liquid is 1.5 to 6 mol / L, preferably 3 to 6 mol / L; and / or the immersion temperature is 15 to 35° C., and the immersion time is 30 to 90 min; and / or the Zeta potential of the aluminum foil surface after immersion is ≥-1 mV.

[0010] Furthermore, in the above step S3, inert gas Ar gas is used for cleaning during the cleaning process, and / or the purity of Ar gas is ≥99.9%; and / or, during the sintering process, nitrogen gas is used for protection, the concentration of nitrogen gas is ≥99.99%, the sintering temperature is 400-600°C; and / or the insulation time is 3-12h.

[0011] Furthermore, in the above step S2, the surface of the aluminum foil after ultrasound contains hydroxyl groups, and the mass of the hydroxyl groups is 0.1mmol / g to 0.2mmol / g of the mass of the aluminum foil after ultrasound; or the Zeta potential of the aluminum foil after ultrasound is less than -2mV; the temperature of the ultrasonic treatment is 45 to 75°C, the time of the ultrasonic treatment is 60 to 180min, and the wave frequency of the ultrasonic treatment is 45 to 65kHz.

[0012] Furthermore, in the above step S1, the thickness of the surface oxide film of the aluminum foil after pretreatment is 10 to 20 nm.

[0013] Further, the above step S1 includes: step S11, using an acidic degreasing agent to perform acid degreasing treatment on the aluminum foil to obtain the aluminum foil after acid degreasing; step S12, performing alkaline etching treatment on the aluminum foil after acid degreasing in an electrolytic cell filled with sodium hydroxide solution to obtain the aluminum foil after alkaline etching; step S13, using a nitric acid solution to neutralize the aluminum foil after alkaline etching to obtain the neutralized aluminum foil; step S14, anodizing the neutralized aluminum foil in an electrolytic cell filled with an acidic solution containing aluminum ions to obtain the aluminum foil after anodizing; step S15, washing the aluminum foil after anodizing with deionized water to obtain the aluminum foil after pretreatment; wherein the acidic degreasing agent includes a degreasing agent and an acidic solution, and the degreasing agent includes 1.5-3wt% of phosphoric acid, 0.4-0.6wt% of sodium dodecylbenzene sulfonate, 0.1-0.3wt% of sodium dodecylbenzene sulfate and 0.2-0.7wt% of ferric sulfate. Acidic aqueous solution, the acidic solution is a 10-20wt% sulfuric acid solution; and / or the temperature of the acid degreasing treatment is 25-30°C, and the time of the acid degreasing treatment is 3-5min; and / or the mass concentration of the sodium hydroxide solution is 30-45g / L, and / or the temperature of the alkaline etching treatment is 40-60°C; and / or the mass concentration of the nitric acid solution is 100-120g / L, the temperature of the neutralization treatment is 25-30°C, and the time of the neutralization treatment is 5-15s; and / or the aluminum ion-containing acidic solution includes a mixed solution of sulfuric acid solution and aluminum salt solution, wherein the mass concentration of the sulfuric acid solution is 150-180g / L; and / or the mass concentration of the aluminum salt solution is 5-15g / L, and the aluminum salt solution is aluminum sulfate solution and / or aluminum chloride solution; and / or the temperature of the anodizing is 18-22°C, the voltage of the anodizing is 14-18V, and the current density of the anodizing is 0.2-0.6A / dm 2 , the anodizing time is 10 to 200 seconds; and / or, when the pH of the deionized water obtained by washing is greater than 6.8, and the concentration of Al ions in the deionized water obtained by washing is lower than 0.001 g / L, the washing is stopped.

[0014] According to another aspect of the present invention, a lithium-ion battery is provided, comprising a positive electrode, a negative electrode and an electrolyte, wherein the positive electrode comprises a positive electrode current collector and a positive electrode active material coating, the electrolyte comprises a lithium salt, and the lithium salt comprises LiFSI and / or LiTFSI, and the positive electrode current collector is the aforementioned composite aluminum current collector, wherein the resistivity of the positive electrode after rolling is 0.1 to 1 Ω·m.

[0015] By applying the technical solution of the present invention, the core principle of the composite aluminum current collector involved in the present application is to coat a layer of AlN passivation film on the surface of the aluminum foil. Since AlN has good electronic conductivity, high chemical stability and high voltage resistance, it can meet the requirements of conductivity and corrosion resistance at the same time. Therefore, coating a layer of AlN passivation film on the surface of the aluminum foil is not only conducive to reducing the problem of corrosion of the aluminum foil at high voltage, but also conducive to improving the conductivity of the current collector, thereby meeting the needs of high-power batteries. BRIEF DESCRIPTION OF THE DRAWINGS

[0016] The drawings constituting a part of the present application are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute an improper limitation of the present invention. In the drawings:

[0017] Figure 1 A schematic diagram of the preparation process of the composite aluminum current collector of the present application is shown. DETAILED DESCRIPTION

[0018] It should be noted that, in the absence of conflict, the embodiments and features in the embodiments of the present application can be combined with each other. The present invention will be described in detail below with reference to the accompanying drawings and in combination with the embodiments.

[0019] As analyzed in the background technology of this application, there are problems in the prior art that aluminum foil is corroded at high voltage and the conductivity of the current collector cannot meet the requirements of high-power batteries. In order to solve this problem, this application provides a composite aluminum current collector, a preparation method thereof, and a lithium-ion battery.

[0020] In a typical embodiment of the present application, a composite aluminum current collector is provided. The composite aluminum current collector includes an aluminum foil and an AlN passivation film coated on the surface of the aluminum foil.

[0021] The core principle of the composite aluminum current collector involved in the present application is to coat a layer of AlN passivation film on the surface of the aluminum foil. Since AlN has good electronic conductivity, high chemical stability and high voltage resistance, it can meet the requirements of conductivity and corrosion resistance at the same time. Therefore, coating a layer of AlN passivation film on the surface of the aluminum foil is not only conducive to reducing the problem of corrosion of the aluminum foil at high voltage, but also conducive to improving the conductivity of the current collector, thereby meeting the needs of high-power batteries.

[0022] In one embodiment of the present application, the thickness of the AlN passivation film layer is 5 to 15 nm, preferably 8.9 to 15 nm.

[0023] If the AlN passivation film is too thin, it may not provide sufficient protection, while if the AlN passivation film is too thick, it may increase the electronic internal resistance; therefore, it is preferred to control the thickness of the AlN passivation film layer within the above range, which is not only beneficial to reduce the oxidative corrosion of the aluminum foil under high voltage, but also beneficial to reduce the impact on the battery power performance, thereby maximizing the efficiency and cycle life of the battery.

[0024] In one embodiment of the present application, the electrical conductivity of the composite aluminum current collector is 2500-4005 S / m, preferably 3206-4005 S / m; and / or the resistivity of the composite aluminum current collector is not higher than 4×10 -8 Ω·m, preferably 2.69×10 -8 Ω·m~3.56×10 -8 Ω·m.

[0025] It is preferred to control the conductivity of the composite aluminum current collector within the above range, which is beneficial to improving the transmission of electrons, thereby improving the specific capacity and rate performance of the lithium-ion battery. Controlling the resistivity of the composite aluminum current collector is beneficial to improving the charging speed and efficiency, thereby improving the overall performance and reliability of the battery.

[0026] In another typical embodiment of the present application, a method for preparing a composite aluminum current collector is provided, and the preparation method includes: step S1, performing surface pretreatment on an aluminum foil to obtain a pretreated aluminum foil; step S2, using water as a medium, performing ultrasonic treatment on the pretreated aluminum foil to obtain an ultrasonic aluminum foil; step S3, placing the ultrasonic aluminum foil in a trimethylaluminum liquid, soaking, washing, and sintering in sequence to obtain a composite aluminum current collector.

[0027] In the above preparation method of the present application, the surface pretreatment of the aluminum foil is performed, which helps to improve the cleanliness of the surface of the aluminum foil after pretreatment. Using water as a medium, the aluminum foil after pretreatment is ultrasonically treated, and hydroxyl groups can be modified on the surface of the aluminum foil after ultrasound. The aluminum foil after ultrasound is placed in a trimethylaluminum liquid for soaking, cleaning, and sintering in sequence, and an AlN film layer can be generated on the surface of the aluminum foil after ultrasound to obtain a composite aluminum current collector. The AlN film layer can effectively reduce corrosion in high-power electrolytes while maintaining good electronic conductivity, thereby achieving high performance and long life of the battery. In addition, the hydroxyl groups modified on the AlN film layer by ultrasound are conducive to modifying the bonding force between the AlN film layer and the aluminum foil.

[0028] In one embodiment of the present application, in the above step S3, the concentration of trimethylaluminum liquid is 1.5-6 mol / L, preferably 3-6 mol / L; and / or the immersion temperature is 15-35°C, the immersion time is 30-90 min; and / or, the Zeta potential of the aluminum foil surface after immersion is ≥-1 mV.

[0029] The concentration of the trimethylaluminum liquid is preferably controlled within the above range, which is conducive to increasing the formation rate of the AlN film layer. The immersion temperature and immersion time are preferably controlled within the above range, which is conducive to forming a more uniform and stable AlN passivation film, which is not only conducive to improving the corrosion resistance of the aluminum foil, but also conducive to improving the stable operation of the battery under high power conditions. Controlling the Zeta potential of the aluminum foil surface after immersion to be ≥-1mV is conducive to the molecular adsorption of the trimethylaluminum solution in the subsequent steps.

[0030] In one embodiment of the present application, in the above step S3, inert gas Ar gas is used for cleaning during the cleaning process, and / or the purity of Ar gas is ≥99.9%; and / or, during the sintering process, nitrogen gas is used for protection, the concentration of nitrogen gas is ≥99.99%, the sintering temperature is 400-600°C; and / or the insulation time is 3-12h.

[0031] Using inert gas Ar gas for cleaning and controlling the purity of Ar gas ≥99.9% is beneficial to improving the cleanliness of the aluminum foil surface before sintering. It is preferred to control nitrogen gas for protection, and the sintering temperature and insulation time are within the above conditions, which is beneficial to improving the purity and stability of the AlN passivation film. The high-purity AlN passivation film can significantly reduce the risk of oxidative corrosion of the aluminum foil under high voltage. At the same time, it is also beneficial to improve the conductivity of the AlN passivation film, thereby maintaining the high power performance of the battery.

[0032] In one embodiment of the present application, in the above step S2, the surface of the aluminum foil after ultrasound contains hydroxyl groups, and the mass of the hydroxyl groups is 0.1mmol / g to 0.2mmol / g of the mass of the aluminum foil after ultrasound; and / or the Zeta potential of the aluminum foil after ultrasound is <-2mV; the temperature of the ultrasonic treatment is 45 to 75°C, the time of the ultrasonic treatment is 60 to 180min, and the wave frequency of the ultrasonic treatment is 45 to 65kHz.

[0033] Ultrasonic treatment can increase the number of hydroxyl functional groups on the surface of the aluminum foil. It is preferred to control the temperature, time and wave frequency of the ultrasonic treatment within the above range, which is conducive to the subsequent adsorption of trimethylaluminum (TMA), thereby facilitating the formation of a denser AlN passivation film. By controlling the mass of the hydroxyl group within the above range, the formed AlN film has better adhesion and stability, which is conducive to reducing the risk of oxidative corrosion of the aluminum foil under high voltage, and is also conducive to maintaining the high power performance of the battery. The Zeta potential of the aluminum foil after ultrasound should be controlled to be less than -2mV, which is conducive to the molecular adsorption of the trimethylaluminum solution in the subsequent steps.

[0034] In one embodiment of the present application, in the above step S1, the thickness of the surface oxide film of the aluminum foil after pretreatment is 10 to 20 nm.

[0035] It is preferred to control the thickness of the oxide film on the surface of the aluminum foil after pretreatment within the above range, which is conducive to reasonably controlling the thickness of the subsequently generated AlN film and preventing the current collector conductivity from decreasing too much while ensuring the inertness of the current collector interface.

[0036] In one embodiment of the present application, the above-mentioned step S1 includes: step S11, using an acidic degreasing agent to perform acid degreasing treatment on the aluminum foil to obtain the aluminum foil after acid degreasing; step S12, performing alkaline etching treatment on the aluminum foil after acid degreasing in an electrolytic cell filled with sodium hydroxide solution to obtain the aluminum foil after alkaline etching; step S13, using a nitric acid solution to neutralize the aluminum foil after alkaline etching to obtain the neutralized aluminum foil; step S14, anodizing the neutralized aluminum foil in an electrolytic cell filled with an acidic solution containing aluminum ions to obtain the aluminum foil after anodizing; step S15, washing the aluminum foil after anodizing with deionized water to obtain the aluminum foil after pretreatment; wherein the acidic degreasing agent includes a degreasing agent and an acidic solution, and the degreasing agent includes 1.5-3wt% of phosphoric acid, 0.4-0.6wt% of sodium dodecylbenzene sulfonate, 0.1-0.3wt% of sodium dodecylbenzene sulfate and 0.2-0.7wt% of sulfuric acid. Acidic aqueous solution of iron, the acidic solution is a 10-20wt% sulfuric acid solution; and / or the temperature of the acid degreasing treatment is 25-30°C, and the time of the acid degreasing treatment is 3-5min; and / or the mass concentration of the sodium hydroxide solution is 30-45g / L, and / or the temperature of the alkaline etching treatment is 40-60°C; and / or the mass concentration of the nitric acid solution is 100-120g / L, the temperature of the alkaline etching treatment is 25-30°C, and the time of the alkaline etching treatment is 5-15s; and / or the acidic solution containing aluminum ions includes a mixed solution of sulfuric acid solution and aluminum salt solution, wherein the mass concentration of the sulfuric acid solution is 150-180g / L; and / or the mass concentration of the aluminum salt solution is 5-15g / L, and the aluminum salt solution is aluminum sulfate solution and / or aluminum chloride solution; and / or the temperature of the anodizing is 18-22°C, the voltage of the anodizing is 14-18V, and the current density of the anodizing is 0.2-0.6A / dm 2 , the anodizing time is 10 to 200 seconds; and / or, when the pH of the deionized water obtained by washing is greater than 6.8, and the concentration of Al ions in the deionized water obtained by washing is lower than 0.001 g / L, the washing is stopped.

[0037] The surface of the neutralized aluminum foil obtained by the treatment of step S11 to step S13 has no oxide film. It is preferred to control the conditions of acid degreasing treatment, alkaline etching treatment and neutralization in order to help remove the original thick oxide film on the surface of the aluminum foil. Through step S14 and step S15, the surface of the pretreated aluminum foil is provided with an oxide film with controllable thickness, and it is preferred to control the conditions of anodization in order to more accurately control the thickness of the surface oxide film of the aluminum foil after pretreatment. Comprehensive control of the steps and conditions of the pretreatment process within the above range is conducive to removing impurities and oxide layers on the surface of the aluminum foil, thereby forming a uniform oxide film with controllable thickness, thereby providing an ideal substrate for the subsequent formation of an AlN passivation film, and then facilitating the formation of an AlN passivation film with uniform thickness and stable structure, further improving the anti-oxidation corrosion ability of the aluminum current collector, and also conducive to the electrical conductivity of the current collector meeting the needs of high-power batteries.

[0038] In another typical embodiment of the present application, a lithium-ion battery is provided, comprising a positive electrode, a negative electrode and an electrolyte, wherein the positive electrode comprises a positive electrode current collector and a positive electrode active material coating, the electrolyte comprises a lithium salt, and the lithium salt comprises LiFSI and / or LiTFSI, and the positive electrode current collector is the above-mentioned composite aluminum current collector, wherein the resistivity of the positive electrode after rolling is 0.1 to 1 Ω·m.

[0039] The composite aluminum current collector with high chemical stability and high voltage resistance is used, which is particularly not corroded in electrolytes including LiFSI and / or LiTFSI, and can also keep the resistance of the positive electrode within a smaller range, so that the lithium-ion battery can operate under high power and high voltage conditions, while maintaining a low internal resistance and having good cycle performance and rate performance. It is preferred to control the resistance of the positive electrode sheet within the above range, and further, it is preferred that the resistivity of the positive electrode after rolling is 0.13 to 0.2Ω·m, which is conducive to further improving the rate performance of the lithium-ion battery.

[0040] The beneficial effects of the present application will be further illustrated below in conjunction with embodiments.

[0041] Example 1

[0042] At 25°C, the aluminum foil was placed in an electrolytic tank filled with phosphoric acid and sulfuric acid solution for acid degreasing treatment (including degreasing agent and acidic solution), wherein the degreasing agent was an acidic aqueous solution of 2wt% phosphoric acid, 0.5wt% sodium dodecylbenzene sulfonate, 0.2wt% sodium dodecylbenzene sulfate and 0.5wt% ferric sulfate, and the acidic solution was a 15wt% sulfuric acid solution. After 3 minutes, the aluminum foil was taken out; at 60°C, the aluminum foil after acid degreasing was placed in a hydrogen peroxide with a mass concentration of 45g / L. Alkaline etching was performed in a sodium oxide solution, and the aluminum foil was taken out after the alkaline etching was completed; at 30°C, the aluminum foil after alkaline etching was placed in a nitric acid solution with a mass concentration of 100g / L for neutralization, and the aluminum foil was taken out after 15s; at 22°C, the neutralized aluminum foil was placed in a mixed solution of a sulfuric acid solution with a mass concentration of 160g / L and an aluminum sulfate solution with a mass concentration of 15g / L for anodization, wherein the anodization voltage was 15V and the anodization current density was 0.3A / dm 2 After 100s, the aluminum foil was taken out and washed with deionized water. When the pH of the deionized water obtained by washing was greater than 6.8 and the concentration of Al ions in the deionized water obtained by washing was lower than 0.001g / L, the washing was stopped to obtain the pretreated aluminum foil, and the thickness of the surface oxide film was 10nm.

[0043] The aluminum foil after the above pretreatment was ultrasonically treated in water at 60°C, the wave frequency of the ultrasonic treatment was 50kHz, and the ultrasonic treatment was stopped after 120 minutes. The Zeta potential of the aluminum foil after ultrasonic treatment was -2.5mV. After taking out the aluminum foil, it was immersed in a trimethylaluminum liquid solution with a concentration of 3mol / L, wherein the immersion temperature was 25°C, and the aluminum foil was taken out after immersion for 60 minutes. The Zeta potential of the aluminum foil surface after immersion was -0.5mV; the aluminum foil was cleaned with an inert gas Ar gas with a purity of ≥99.9%. After cleaning, the aluminum foil was sintered in a nitrogen atmosphere with a purity of ≥99.99%, and the sintering temperature was 450°C, and the temperature was kept for 10 hours to finally obtain a composite aluminum current collector.

[0044] Example 2

[0045] The difference from Example 1 is that the concentration of the trimethylaluminum liquid is 1.5 mol / L, the Zeta potential of the aluminum foil surface after immersion is -0.8 mV, and a composite aluminum current collector is finally obtained.

[0046] Example 3

[0047] The difference from Example 1 is that the concentration of the trimethylaluminum liquid is 6 mol / L, the Zeta potential of the aluminum foil surface after immersion is -0.5 mV, and a composite aluminum current collector is finally obtained.

[0048] Example 4

[0049] The difference from Example 1 is that the sintering temperature is 350° C., and a composite aluminum current collector is finally obtained.

[0050] Example 5

[0051] The difference from Example 1 is that the sintering temperature is 550° C., and a composite aluminum current collector is finally obtained.

[0052] Example 6

[0053] The difference from Example 1 is that the sintering temperature is 600° C., and a composite aluminum current collector is finally obtained.

[0054] Example 7

[0055] The difference from Example 1 is that the temperature of ultrasonic treatment is 45° C., the wave frequency of ultrasonic treatment is 45 kHz, the Zeta potential of the aluminum foil after ultrasonic treatment is -3 mV, and finally a composite aluminum current collector is obtained.

[0056] Example 8

[0057] The difference from Example 1 is that the temperature of ultrasonic treatment is 75° C., the wave frequency of ultrasonic treatment is 65 kHz, the Zeta potential of the aluminum foil after ultrasonic treatment is -3.2 mV, and finally a composite aluminum current collector is obtained.

[0058] Example 9

[0059] The difference from Example 1 is that the temperature of ultrasonic treatment is 90° C., the wave frequency of ultrasonic treatment is 80 kHz, the Zeta potential of the aluminum foil after ultrasonic treatment is -3.6 mV, and finally a composite aluminum current collector is obtained.

[0060] Example 10

[0061] The difference from Example 1 is that the voltage of the anodic oxidation is 14 V, and a composite aluminum current collector is finally obtained.

[0062] Embodiment 11

[0063] The difference from Example 1 is that the voltage of the anodic oxidation is 18 V, and a composite aluminum current collector is finally obtained.

[0064] Example 12

[0065] The difference from Example 1 is that the voltage of the anodic oxidation is 13 V, and a composite aluminum current collector is finally obtained.

[0066] Embodiment 13

[0067] The difference from Example 1 is that the current density of the anodic oxidation is 0.6A / dm 2 , and finally a composite aluminum current collector is obtained.

[0068] Embodiment 14

[0069] The difference from Example 1 is that the current density of the anodic oxidation is 0.15 A / dm 2 , and finally a composite aluminum current collector is obtained.

[0070] Comparative Example 1

[0071] The difference from Example 1 is that the aluminum foil is not treated in any way and is directly used as an aluminum current collector.

[0072] Comparative Example 2

[0073] The difference from Example 1 is that the pretreated aluminum foil is directly used as the aluminum current collector.

[0074] The side cross-section of the current collector was observed using a scanning electron microscope to determine the thickness of the AlN passivation film layer of the composite aluminum current collector obtained in the above embodiments and comparative examples. The conductivity of the composite aluminum current collector obtained in the above embodiments and comparative examples was tested using a conductivity testing instrument. The resistivity of the composite aluminum current collector obtained in the above embodiments and comparative examples was tested with reference to ASTM B193-16, and the test results are listed in Table 1.

[0075] The content of hydroxyl groups on the surface of the aluminum foil after ultrasonic treatment obtained in the above examples was calculated, and the results are listed in Table 1.

[0076] The composite aluminum current collectors obtained in the above examples and comparative examples were respectively 0.88 Co 0.04 Mn 0.08 O2, a conductive agent and a binder are used to prepare a positive electrode. The resistance of the obtained positive electrode is tested by a film resistance meter. The test results are listed in Table 1. The test method refers to the national standard GB_T-33143-2022.

[0077] The composite aluminum current collectors obtained in the above examples and comparative examples were respectively 0.88 Co 0.04 Mn 0.08 The positive electrode prepared by O2 (96wt%), SuperP conductive agent (1.5wt%), polyvinylidene fluoride (PVDF, 2.5wt%), and the graphite / silicon oxide (mass ratio 9:1) composite negative electrode (active material 97wt%, binder: SBR content (1wt%) + CMCNa (1wt%), conductive agent: SP, content 1wt%) and carbonate electrolyte (1Mol / L LiFSI, solvent EC:EMC:DMC (the volume ratio of the three is 3:1:6) were assembled into a lithium-ion battery, and the power and rate performance of the lithium-ion battery under 0.33, 0.5C, and 1C current conditions were tested, and the test results are listed in Table 2.

[0078] Table 1

[0079]

[0080] Table 2

[0081]

[0082]

[0083] From the above description, it can be seen that the above embodiments of the present invention achieve the following technical effects:

[0084] The core principle of the composite aluminum current collector involved in the present application is to coat a layer of AlN passivation film on the surface of the aluminum foil. Since AlN has good electronic conductivity, high chemical stability and high voltage resistance, it can meet the requirements of conductivity and corrosion resistance at the same time. Therefore, coating a layer of AlN passivation film on the surface of the aluminum foil is not only conducive to reducing the problem of corrosion of the aluminum foil at high voltage, but also conducive to improving the conductivity of the current collector, thereby meeting the needs of high-power batteries.

[0085] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A composite aluminum current collector, characterized in that: The composite aluminum current collector comprises an aluminum foil and an AlN passivation film coated on the surface of the aluminum foil.

2. The composite aluminum current collector according to claim 1, characterized in that: The thickness of the AlN passivation film layer is 5 to 15 nm, preferably 8.9 to 15 nm.

3. The composite aluminum current collector according to claim 1 or 2, characterized in that: The electrical conductivity of the composite aluminum current collector is 2500-4005 S / m, preferably 3206-4005 S / m; and / or the resistivity of the composite aluminum current collector is not higher than 4×10 -8 Ω·m, preferably 2.69×10 -8 Ω·m~3.56×10 -8 Ω·m.

4. A method for preparing the composite aluminum current collector according to any one of claims 1 to 3, characterized in that: The preparation method comprises: Step S1, performing surface pretreatment on the aluminum foil to obtain pretreated aluminum foil; Step S2, using water as a medium, subjecting the pretreated aluminum foil to ultrasonic treatment to obtain an ultrasonicated aluminum foil; Step S3, placing the ultrasonically treated aluminum foil into trimethylaluminum liquid for soaking, cleaning, and sintering in sequence to obtain a composite aluminum current collector.

5. The method for preparing the composite aluminum current collector according to claim 4, characterized in that: In step S3, the concentration of the trimethylaluminum liquid is 1.5 to 6 mol / L, preferably 3 to 6 mol / L; and / or the immersion temperature is 15 to 35° C., and the immersion time is 30 to 90 min; and / or the Zeta potential of the aluminum foil surface after immersion is ≥-1 mV.

6. The method for preparing the composite aluminum current collector according to claim 4 or 5, characterized in that: In the step S3, inert gas Ar gas is used for cleaning during the cleaning process, and / or the purity of the Ar gas is ≥99.9%; and / or, nitrogen gas is used for protection during the sintering process, the concentration of the nitrogen gas is ≥99.99%, the sintering temperature is 400-600°C; and / or the insulation time is 3-12h.

7. The method for preparing a composite aluminum current collector according to any one of claims 4 to 6, characterized in that: In the step S2, the surface of the aluminum foil after ultrasound contains hydroxyl groups, and the mass of the hydroxyl groups is 0.1 mmol / g to 0.2 mmol / g of the mass of the aluminum foil after ultrasound; or the Zeta potential of the aluminum foil after ultrasound is less than -2 mV; The temperature of the ultrasonic treatment is 45-75° C., the time of the ultrasonic treatment is 60-180 min, and the wave frequency of the ultrasonic treatment is 45-65 kHz.

8. The method for preparing the composite aluminum current collector according to claim 4, characterized in that: In the step S1, the thickness of the surface oxide film of the aluminum foil after the pretreatment is 10 to 20 nm.

9. The method for preparing the composite conductive paste according to claim 4 or 5, characterized in that: The step S1 comprises: Step S11, performing an acid degreasing treatment on the aluminum foil using an acid degreasing agent to obtain an acid degreased aluminum foil; Step S12, subjecting the aluminum foil after the acid degreasing to alkaline etching in an electrolytic cell filled with a sodium hydroxide solution to obtain an alkaline-etched aluminum foil; Step S13, neutralizing the alkali-etched aluminum foil with a nitric acid solution to obtain a neutralized aluminum foil; Step S14, anodizing the neutralized aluminum foil in an electrolytic cell filled with an acidic solution containing aluminum ions to obtain an anodized aluminum foil; Step S15, washing the anodized aluminum foil with deionized water to obtain the pretreated aluminum foil; The acidic degreasing agent comprises a degreasing agent and an acidic solution, wherein the degreasing agent comprises an acidic aqueous solution of 1.5-3wt% phosphoric acid, 0.4-0.6wt% sodium dodecylbenzene sulfonate, 0.1-0.3wt% sodium dodecylbenzene sulfate and 0.2-0.7wt% ferric sulfate, and the acidic solution is a 10-20wt% sulfuric acid solution; and / or the temperature of the acidic degreasing treatment is 25-30°C, and the time of the acidic degreasing treatment is 3-5min; and / or, the mass concentration of the sodium hydroxide solution is 30-45 g / L, and / or the temperature of the alkaline etching treatment is 40-60° C.; And / or, the mass concentration of the nitric acid solution is 100-120 g / L, the temperature of the neutralization treatment is 25-30° C., and the time of the neutralization treatment is 5-15 s; And / or, the aluminum ion-containing acidic solution comprises a mixture of a sulfuric acid solution and an aluminum salt solution, wherein the mass concentration of the sulfuric acid solution is 150-180 g / L; and / or the mass concentration of the aluminum salt solution is 5-15 g / L, and the aluminum salt solution is an aluminum sulfate solution and / or an aluminum chloride solution; and / or, the temperature of the anodization is 18 to 22° C., the voltage of the anodization is 14 to 18 V, and the current density of the anodization is 0.2 to 0.6 A / dm 2 , the anodizing time is 10 to 200 seconds; And / or, when the pH of the deionized water obtained by the cleaning is greater than 6.8, and the concentration of Al ions in the deionized water obtained by the cleaning is lower than 0.001 g / L, the cleaning is stopped.

10. A lithium-ion battery comprising a positive electrode, a negative electrode and an electrolyte, wherein the positive electrode comprises a positive electrode current collector and a positive electrode active material coating, and the electrolyte comprises a lithium salt, wherein the lithium salt comprises LiFSI and / or LiTFSI, wherein: The positive electrode current collector is the composite aluminum current collector according to any one of claims 1 to 3, wherein the resistivity of the positive electrode after rolling is 0.1 to 1 Ω·m.